Complement C3c and C4c as predictors of death in heart failure - Silva, N (2015)
Background: Activation of the immune system is one of the several pathways suggested as involved in Heart Failure (HF). The complement system is a key component of innate immunity. We hypothesized that complement proteins C3 and C4 can be an important predictor of death in patients with this condition. Methods: 380 patients admitted with acute HF were recruited. They were followed up during 6 months. Serum C3c and C4c proteins were measured and groups were created and compared according to the 25th percentile cut-off value. A multivariate Cox-regression model was used to establish the prognostic value of both markers with the endpoints of HF and all-cause death. Results: Median patients' age was 78 years and 49% of the patients were men. No major differences were observed in clinical characteristics of the groups. Patients with lower values of C3c and C4c had significantly higher values of BNP. During the 6 month period of follow up, 63 patients died, and 49 patients were due to HF. C4c showed univariate prognostic value, but not multivariate value. The multivariate-adjusted Hazard Ratios for the 6 month HF and all-cause death in patients with C3c values below 110.0 mg/dL were, respectively, 2.32 (95% CI: 1.25–4.28) and 2.52 (95% CI: 1.41–4.49). Conclusion: Lower C3c levels are independently associated with higher risk of death. Our results reinforce the role of innate immunity in HF pathophysiology.